Prediction of Enhanced Dimerization inside Dilute Alloy Nanoparticles - Micha Polak; Leonid Rubinovich (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2017)
According to a unique nano-confinement effect of entropic origin, predicted by us several years ago for the equilibrium state of chemical reactions, the equilibrium-constant and extent are greatly enhanced depending on the small number of molecules involved, and for many reactions also on the nano-space size. This work explored the validity of this effect in the case of elemental dimerization reactions within dilute alloy nanoparticles with separation tendency, Pd - Ir cuboctahedra in particular. Employing a simple model for the system energetics, computations based on the exact canonical partition-function reveal nano-confinement induced Ir2 dimer stabilization within Pd surface segregated nanoparticles, reflected e.g., by up to ~ 60% increased dimerization extent and by doubling of the 1n KD vs. 1/T slope, as compared to the macroscopic thermodynamic limit. The dual role of the configurational entropy, namely mixing of Ir/Ir2 vs. Pd/Ir is elucidated. Study based on more elaborate energetic models is desirable as the next step of this research.